Multidimensional scorecard: adjustments to the bsc from the approach to stakeholder theory. design proposal for public enterprise the rail freight in renfe-operadora -Spain (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
This paper focuses a demonstration of the adjustments made to the Balanced Scorecard (BSC) for transformation into an instrument of practical feasibility for the management of public organizations. Theory of Stakeholders possible to define a multidimensional model to guide the management public in terms of responding to the demands and requirements of different interest groups, primarily the community or users that require improvements in public service delivery. This proposed model has been called Multidimensional Scorecard (MSC) and empirical evidence has been selected the application of in the public enterprise of rail freight in Renfe-Operadora (Spain), shall provide the freight service by rail and since 2004 to the present, is undergoing a process of change and institutional pressures.
Keywords: balanced scorecard; stakeholders; public organizations